POSTURE MEASUREMENT AND BIOMECHANICAL COMPUTER SYNTHESIS OF HUMAN MOTIONS - N. B. Sotsky (Приборы и методы измерений, 2015)
The paper proposes a novel approach to the study of physical exercise, which has at its core measurement parameters determining the pose of a man, and then use this information as a basis for computer synthesis of motor actions. The proposed method makes it possible to identify the major components of motor actions, such as the elements of posture and movement control joints, build effective teaching methods, improving its performance.